Psoriasis and Atopic Dermatitis. Issue 1 (January 2017) - Griffiths, Christopher; van de Kerkhof, Peter; Czarnecka-Operacz, Magdalena
Abstract Psoriasis and atopic dermatitis are common, chronic inflammatory skin diseases. We discuss several aspects of these disorders, including: risk factors; incidence and prevalence; the complex disease burden; and the comorbidities that increase the clinical significance of each disorder. We also focus on treatment management strategies and outline why individualized, patient-centered treatment regimens should be part of the care plans for patients with either psoriasis or atopic dermatitis. Finally, we conclude that, while our theoretical knowledge of the optimum care plans for these patients is increasingly sophisticated, this understanding is, unfortunately, not always reflected in daily clinical practice.